2020
DOI: 10.1007/978-1-0716-0779-4_13
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Recovery After Photobleaching to Study the Dynamics of Membrane-Bound Proteins In Vivo Using the Drosophila Embryo

Abstract: The epithelial-to-mesenchymal transition is a highly dynamic cell process and tools such as Fluorescence recovery after photobleaching (FRAP), which allow the study of rapid protein dynamics, enable the following of this process in vivo. This technique uses a short intense pulse of photons to disrupt the fluorescence of a tagged protein in a region of a sample. The fluorescent signal intensity after this bleaching is then recorded and the signal recovery used to provide an indicator of the dynamics of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…9M). In wildtype, recovery was roughly similar to what others have observed (Cliffe et al ., 2004; Greig and Bulgakova, 2021)—recovery plateaued after 400-500 seconds and the mobile fraction was about 75%. We then repeated this analysis in M/Z pyd mutants.…”
Section: Resultsmentioning
confidence: 98%
“…9M). In wildtype, recovery was roughly similar to what others have observed (Cliffe et al ., 2004; Greig and Bulgakova, 2021)—recovery plateaued after 400-500 seconds and the mobile fraction was about 75%. We then repeated this analysis in M/Z pyd mutants.…”
Section: Resultsmentioning
confidence: 98%
“…We found that AP-1 depletion halved the halftime of the slow component’s recovery ( Figure 7B ). E-cad recovery following AP-1 depletion was best-fitted by a single exponential model, likely as the slow halftime reduction made it impossible to confidently separate the components ( Greig and Bulgakova, 2021 ). The halftime of a diffusion-uncoupled recovery depends only on the reaction off-rate (internalization rate in this case) ( Sprague and McNally, 2005 ; Iyer et al.…”
Section: Resultsmentioning
confidence: 99%
“…The recovery curves were obtained by manually measuring intensities of background, control region, and photobleached region using 2-µm-diameter circular regions for each time point in Fiji. The raw data were processed as in Greig and Bulgakova (2021) to obtain the normalized recovery curves, namely following background subtraction the intensity at the bleached spot was normalized to the intensities of a control area at the same time point and the bleached area before bleaching.…”
Section: Methodsmentioning
confidence: 99%
“…We found that AP-1 depletion halved the halftime of the slow component's recovery (Fig 7B). Ecad recovery following AP-1 depletion was best-fit by a single exponential model, likely as the slow halftime reduction made it impossible to confidently separate the components [61].…”
Section: Resultsmentioning
confidence: 99%
“…The recovery curves were obtained by manually measuring intensities of background, control region, and photobleached region using 2-µm diameter circular regions for each time point in Fiji. The raw data was processed as in [61] to obtain the normalized recovery curves, namely following background subtraction the intensity at the bleached spot was normalized to the intensities of a control area at the same time point and the bleached area before bleaching.…”
Section: Frapmentioning
confidence: 99%